Role of scavengers in providing non-material contributions to people - Aguilera-Alcalá, Natividad; Morales-Reyes, Zebensui; Martín-López, Berta; Moleón, Marcos; Sánchez Zapata, José Antonio (Ecological Indicators, 2020)
In today’s societies, scavengers play an important role as providers of nature’s contribution to people (NCP), such as disease control and carcass removal. Yet very little is known about the non-material NCP (i.e. nature’s effects on subjective and psychological aspects of people’s well-being) that scavengers provide societies with. The first aim of this study is to determine which species of obligate and facultative scavengers provide different nonmaterial NCP in Spain, including recreational and aesthetic experiences, learning and inspiration, and supporting identities. The second aim is to identify which ecological variables determine their capacity to provide the aforementioned non-material NCP. To assess non-material NCP nationwide, data were collected from different sources, including the Internet (websites of nature photography and wildlife watching tours, Global Biodiversity Information Facility, and Google Trends), outreach magazines and scientific articles. A top predator, Canis lupus, followed by an obligate scavenger, Gyps fulvus, were among the most prominent species to provide multiple non-material NCP. Aesthetic experiences were provided mainly by common species, such as Genetta genetta, Milvus migrans and corvids. The NCP of recreation and learning by civil society were provided by threatened and charismatic species, such as C. lupus, Ursus arctos and Aquila adalberti. Knowledge acquired by scientists was provided mainly by meso-carnivores. Finally, the NCP of supporting identities was related with species capable of providing beneficial and detrimental contributions, such as C. lupus and Sus scrofa. Integrating data mined from different sources has allowed it to reveal the interweaving among non-material categories. Recognising that all species of scavengers are essential for providing non-material NCP can raise society’s awareness about their important cultural role and may, hence, contribute to their conservation.